Efeito do tratamento com progesterona sobre a reatividade vascular coronariana dependente do endotélio em ratas espontaneamente hipertensas - Costa, Débora Tacon da (2020)
Progesterone receptors are expressed in the endothelium and vascular smooth muscle and through them progesterone produces important effects such as the direct and indirect formation of vasoactive factors, essential for vascular homeostasis. Although relevant to the cardiovascular system, the role of progesterone is poorly characterized, especially in the essential hypertension model, the SHR (Spontaneously Hipertensive Rats). Therefore, the aim of this study was to evaluate the effects of progesterone treatment on endothelium-dependent coronary vascular reactivity in hypertensive and ovariectomized rats. For this, we used adult SHR rats, divided into 3 groups: Sham, Ovariectomized (OVX) and Ovariectomized + treatment (2 mg / kg / day) with progesterone (OVX-P4) for 15 days. Systolic blood pressure was assessed at the beginning and at the end of treatment by tail plethysmography. The vascular reactivity of the coronary bed was investigated using the modified Langendorff method. After 40 minutes of stabilization, the baseline coronary perfusion pressure (CPP) was recorded and the vascular reactivity of the coronary bed was assessed by constructing a bradykinin (BK) dose-response curve administered in increasing concentrations (0.1- 1000 ng) before and after the infusion of pharmacological inhibitors: non-specific inhibitor of the nitric oxide synthase enzyme - N-nitro-L-arginine methyl ester (L-NAME, 100 µM), non-specific inhibitor of the enzyme cyclooxygenase (COX) - indomethacin (INDO; 2.8 μM) , inhibitor of cytochrome P450 (CYP) - clotrimazole (0.75 μM, CLOT), individually or in combination. All protocols were approved by CEUA-UFES (42/2018). Data were expressed as mean ± standard error of the mean, and analyzed by 2-way ANOVA, followed by Tukey's post hoc (p <0.05). Progesterone did not affect the increase in SBP. The OVX and OVX-P4 groups had higher baseline CPP compared to the SHAM group. BK was able to promote vasodilation in all groups studied. However, we observed that the OVX group showed impairment in BK relaxation compared to the SHAM group and that treatment with progesterone was able to prevent this reduction. The non-specific inhibition of NOS produced greater damage in the Sham group, while the inhibition of COX promoted a greater reduction in relaxation in the OVX-P4 group. The main finding of this study was the ability of progesterone to modulate endothelium-dependent coronary vasodilation in SHR ovariectomized females. The damage caused by hormonal deficiency was prevented by progesterone and it seems that one of the pathways involved is prostanoids.